Pengaruh eWOM (electronic word of mouth) dan Hotel Image Terhadap Keputusan Pembelian Jasa Kamar di Aston Batam Hotel & Residence - Wina Septiananda; Rian Surenda (Lembaga Pengembangan Kinerja Dosen, 2024)
this research is motivated by the discovery of problems related to eWOM, hotel image and purchasing decisions. This type of quantitative research with a causal associative approach (cause and effect) using survey methods. The types of data used are primary and secondary data. The population in this study were guests who had stayed and were staying at Aston batam Hotel & Residence. The sample in the study totaled 120 guests with a sample determination technique, namely non probability sampling. Techniques for collecting data through a questionnaire (questionnaire) using a Likert scale that has been tested for validity and reliability. The data from this study were processed with the help of SPSS 18.00. The results of the study show that the eWOM variable is in the good category based on statistical calculations with an average TCR value of 81.5. The hotel image variable is in a good category based on statistical calculations with an average TCR value of 80.4. The Purchasing Decision variable is in the good category based on statistical calculations with an average TCR value of 80.84. At the eWOM (X1) value, Beta or Standardized Coefficient was achieved, namely 0.388 accompanied by T count (4.817) where significance was achieved 0.000 <0.05, so the eWOM variable (X1) contributed a positive and also significant influence on purchasing decisions (Y), then the hypothesis of hotel image research (X2) achieved Beta or Standardized Coefficient whose value was 0.536 accompanied by T count (6.654) where significance was achieved 0.000 <0.05, so the hotel image variable (X2) contributed a positive and also significant influence on purchasing decisions (Y). Next, the Adjusted R Square number whose value is 0.791 means that the contribution of the influence of the independent variable on the dependent variable is 79.1%, while the remaining 20.9% is influenced by other variables.